Analisis Kesantunan Berbahasa dalam Debat Kelima Calon Presiden 2024: Kajian Pragmatik - Lubis, Certika Novianty; Erfiani Baroroh, Hilma (LP2M IAIN Ambon, 2024)
This research is undermined by the importance of understanding the language chaos applied in the context of political debate. The aim of this study is to describe the principle of linguistic chaos and to analyze the chaos of the presidential candidates in the fifth debate in 2024 using the theory of chaos principle. The methods used in this research are qualitative descriptive with data reduction techniques, data classification, and analysis of linguistic fluency. Based on the data analysis, it can be concluded that in the debate of the fifth presidential candidate in 2024 there was more compliance with Leech's principle of compliance because of 51 data, there were 42 data matching compliance of language compliance at 82.3% with indicators 5 maxims of wisdom; 10 maxims of charity; 8 maxims of appreciation; 9 maxims of simplicity; 7 maxims permufaction; and 3 maxims sympathy. Out of the six categories, the author also found some violations in the maxims, such as 3 maxims of wisdom, 4 maxims for charity, and 2 maxims permufaction. Keywords: Debate, maxim, pragmatics, presidential candidate, election